Diagnostic Performance of Computed and Digital Radiography in Fracture Identification (Czech Journal of Multidisciplinary Innovations, 2025)
The x-ray imaging aspect is efficient and effective with little cost involved, which makes it common to be used in many sectors particularly in medical diagnostics. Its quality to pass through body tissues enables it to have clean and non-invasive imaging into the internal body organs and structures. Since it is a vital technology, its evolution became very fast so that today sophisticated X-ray detectors and associated imaging systems have been designed. This research look at two forms of X-Ray imaging devices which are currently being applied in hospitals located within the Kirkuk City in the Kirkuk hospital: Computed Radiography (CR) and Digital Radiography (DR). The study compares the strengths and the weaknesses of the two systems regarding the quality of images produced and performance. A group of bone fracture involvements was diagnosed with the aid of the two technologies. The findings indicated that Digital Radiography (DR) would have been more popularly preferred as it has faster imaging, high quality image production, reduced doses of radiation used and minimum maintenance. The latter features make DR systems more suitable in the contemporary medical environment, where the ability to be fast, accurate, and reliable is essential. In addition, the paper shows the wider applications of higher level of X-ray technology where bone fractures are detected within different areas of the human body which were taken from real cases in the hospital. It also determined that the quality of the pictures taken using CR tend to be less clear when compared to the use of DR